Efficient priming of antigen-specific cytotoxic T lymphocytes by human cord blood dendritic cells. - Salio, M; Dulphy, N; Renneson, J; Herbert, M; McMichael, A; Marchant, A; Cerundolo, V (2003)
Previous studies have suggested that defective immune responses in early life may be related to the immaturity of neonatal antigen-presenting cells. To test this hypothesis, we assessed the capacity of neonatal dendritic cells (DC) to prime and polarize in vitro human naive antigen-specific T cells. We report that mature cord blood DC efficiently prime an oligoclonal population of antigen-specific CD8 T cells, capable of cytolytic activity and IFN-gamma secretion. In contrast, cells primed by immature cord blood DC do not acquire cytolytic activity and secrete lower amounts of IFN-gamma. Upon priming by either immature or mature DC, neonatal T cells acquire markers of activation and differentiation towards effector-memory cells. Our results demonstrate that, if appropriately activated, neonatal DC can prime efficient cytotoxic T lymphocyte (CTL) responses. Furthermore, these findings have important implications for the development of vaccine strategies in early life and for the reconstitution of a functional CTL repertoire after bone marrow transplantation.